The Study of Caregiving with Babysitter on the Ability of Speaking of 2-3 Years Old Children (Descriptive Study is in Puri Hijau Housing Estate Purwokerto, Regency of Banyumas) - Wahyuningtyas, Nuraini; Adiarti, Wulan (BELIA: Early Childhood Education Papers, 2016)
The aim of this study is to describe the caregiving form by babysitter as well as supporting and inhibiting factors of caregiving with babysitter that influence the ability of speaking of 2-3 years old children in Puri Hijau Housing Estate Purwokerto, Regency of Banyumas. This research is a qualitative research of descriptive study research and using methods of observation, interviews and documentation in collecting data. Data analysis techniques is interactive model. Technique of authenticity of data using triangulation technique. According to the result of the research there are some substantive theories that have emerged, namely among others that (1) The Form of Babysitter Caregiving on Speaking Ability of 2-3 years old Children include: Duties as a children’ playing friend and surrogate parents, explaining new words, storytelling contains a message, the nature of authoritarian, democratic and permissive, caregiving combination between parents and babysitter, conversing, eye contact and showing direction, understanding 2 orders, love to asking, storytelling about experience, quiet, argue and cry. (2) Supporting and inhibiting factors affection of caregiving with babysitter on the ability of speaking of 2-3 years old children include: The interference of parents in stimulus, nature and attitude of children to babysitter, cooperation between caregivers and parents, the performance of babysitter, babysitter knowledge about the children speaking ability, babysitter’s patience dealing with children, facilities and infrastructure as well as a family environment, unruly children behavior, attitude of parents, lack of patience babysitter  in the face of a hyperactive child, communication between parents and the babysitter, the minimum caregivers’ knowledge, attitude and nature of the babysitter towards the children.